Factors that influence people's behavior using public transportation in Kerman City, Iran - Bahrein, Azin (2014)
This research aims to find the factors which encourage people to use public transport instead of private car. It also finds the factors that influence people’s behavior regarding the use of public transport in Kerman city of Iran. The case study of this research is Kerman city in Iran. The reason behind selecting Kerman is because of the lack of good and suitable public transportation infrastructure which leads to people’s tendency to use their own car. This tendency is resulted from the fact that car ownership is more convenient, speedy and reliable than public transport. This research tries to find underlying environmental, economic, and psychological problems. By understanding these factors people can save their time and money they spent per day for transportation and also decrease air pollution. This research tries to find these factors by using qualitative and quantitative method based on designing questionnaire to ask from the people of Kerman city. In this case the questionnaire will be given to 100 respondents to answer the questions. Based on their answers, the problems resulting in people’s behavior on using public transportation can be understood. Furthermore, the factors which motivate people to use public transportation will be investigated. Descriptive data analysis was done by using Statistical Package for Social Studies (SPSS) to find the factors that influence people’s behavior regarding the use of public transportation. Based on this analysis there are several factors have been found. Some of these factors include: poor information about schedules of public transportation, long distance, and buses not being attractive and reliable. According to these results, government should concentrate on solving the problems underlying the public transportation system. This will result in higher rate of public transportation usage among the people.